STRATEGI PENGEMBANGAN BMT (BAITUL MAAL WA TAMWIL) DALAM MEMBERDAYAKAN USAHA KECIL MENENGAH - Siswanto, Ely (IQTISHODUNA, 2008)
The sustainability of syariah microfinance institution depends on the organization it professionally, and the strategic implementation comprehensively in positioning BMT (Baitul Maal wa Tamwil) as one of microfinance intermediary institution. The BMT’s existence created positive public image to participate in  developing BMT and improving people wealth broadly. Optimism toward BMT’s prospect is a main capital in developing BMT concept not only  as a development agent, but also as a profit institution who financing of small business enterprise actively. The aim of this research is : 1)to identified and analyst BMT’s model  which can develop the potential of small business enterprise; 2) to describe BMT’s effort to develop potency of small business enterprise.The  result of this research is that BMT development strategy tend to financial viability oriented, institutional soundness oriented and social effect oriented. These strategy must be supported by ability of fiqh and economic analysis and enough resources. Internally, institutional soundness toward financial management  and managerial aspect must be increased by BMT to make small business financing efficiently.